2013
DOI: 10.1103/physrevlett.111.036105
|View full text |Cite
|
Sign up to set email alerts
|

Critical Terrace Width for Two-Dimensional Nucleation during Si Growth on Si(111)-(7×7) Surface

Abstract: The critical terrace width λ for 2D island nucleation and growth (2DNG) on large-scale atomically flat terraces of a step-bunched Si(111)-(7×7) surface has been studied by in situ ultrahigh vacuum reflection electron microscopy as a function of the substrate temperature T and Si deposition rate R. The dependence of λ(2)(R) is characterized by a power law with scaling exponent χ=1.36-1.46, validating an attachment limited (AL) growth kinetics up to 720 °C. At this temperature, the Arrhenius dependencies lnλ(2)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
1
15
1
1
Order By: Relevance
“…Earlier it was shown that the two-dimensional island growth kinetics at the Si(111) surface are characterized by the diffusion-limited regime at a temperature range of 720-1090 o C [60,61]. The critical nucleus size i * was estimated in the range of 1-12 atoms at a low temperature range of 720- Our experimentally obtained value of the critical nucleus size (19-22 atoms) agrees within the error limits of these previously reported values.…”
Section: Surface Kineticssupporting
confidence: 84%
See 1 more Smart Citation
“…Earlier it was shown that the two-dimensional island growth kinetics at the Si(111) surface are characterized by the diffusion-limited regime at a temperature range of 720-1090 o C [60,61]. The critical nucleus size i * was estimated in the range of 1-12 atoms at a low temperature range of 720- Our experimentally obtained value of the critical nucleus size (19-22 atoms) agrees within the error limits of these previously reported values.…”
Section: Surface Kineticssupporting
confidence: 84%
“…The rate-limiting kinetics can be characterized as diffusion-limited (DL) or attachment-detachment limited (ADL) depending on the relative importance of the surface diffusion or the attachment-detachment of the adatoms at the step edge, respectively [50]. Earlier it was shown that the step motion on the Si(111) surface is described by the DL-kinetic regime rather than the ADL conditions [27,39,51]. On the contrary, atomic step kinetics and two-dimensional negative island nucleation on an Si(111) surface in the case of a high concentration of surface vacancies is described by the attachment-detachment kinetics, with the activation energy of the vacancy-step interaction larger than the surface diffusion barrier [12,16,52].…”
Section: Surface Kineticsmentioning
confidence: 99%
“…7b,c) exhibited step growth patterns similar to those observed on surfaces of inorganic [47], [48] and macromolecular [49]–[52] crystals. An example of similar structures observed on the surface of a growing trypsin crystal [53] is shown in Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Some data path bottlenecks were removed in according to parallel architecture optimization technique. In result power consumption was reduced and logic stability was improved [7,[12][13]. This factors helped to use device in different areas such as propulsion engine testing [14], aircrafts, observation balloons and space satellites.…”
Section: Resultsmentioning
confidence: 99%